Impact of a specialist clinical cancer pharmacist at a multidisciplinary lung cancer clinic. Issue 3 (16th September 2014) - Walter, Clare; Mellor, James D; Rice, Carol; Kirsa, Sue; Ball, David; Duffy, Mary; Herschtal, Alan; Mileshkin, Linda
Abstract: Aim: Medication misadventure contributes to unplanned hospital admissions. General practitioners (GPs) may lack experience in managing problems involving complex cancer‐related medication. A previous survey explored the unmet needs of lung cancer outpatients and highlighted their desire for more medication information. Inpatient clinical pharmacy services positively impact on patient care. This study evaluated the effects of extending this service to outpatients. Method: A specialist cancer pharmacist joined the lung cancer clinic team for 6 months. Patients completed assessments of their medication adherence and their satisfaction with the provision of medicine information (at baseline and repeated within 30 days of initial pharmacist review). Following review, a medication list and plan (detailing recommendations/interventions) were provided to patients and their health care providers. Interventions were categorized and graded according to risk avoided. Unplanned admissions and clinic attendance rates were compared with the previous year. GPs' opinion of the service was also evaluated. Results: Forty‐eight patients participated in the study. Medication adherence ( P = 0.007) and patient satisfaction ( P < 0.001) significantly improved. A total of 154 pharmacist interventions were made: 4.5% extreme risk and 43.5% high risk. The mean number of unplanned admissions and clinic attendances per patient decreased from 0.3 to 0.26 ( P = 0.265) and from 3.32 to 2.98 ( P = 0.004), respectively. Seventy‐four percent of surveyed GPs found the service useful. Conclusions: Adding a specialist cancer pharmacist to the outpatient lung cancer team led to significant improvements in patient medication adherence. Both patients and GPs were highly satisfied with the service. Medication misadventure and clinic attendances were reduced.